Landscape and city (Ciudades, 2018)
The history of the relationship between men’s cities and Nature has gone through different times; the country appropriation process developed by cities increases at the Modern Period and, in the XXth century, a very intense urbanization process gave way to the ecological movement birth, showing conservation and sustainability as a matter for concern. Tendencies in the first years of the 21th century present country merged with city into a new and unique landscape, as the result of the appearence of a regional and diffuse city, wher the enclosed open spaces are also completely active; even more, a landscape where the demand for the use of the territory as urban space spreads futher than the city borders. The reading of this XXIst century creation landscape turns out to be the spectator’s own appropriation.
Keywords: history of landscape; urban landscape; regional city; landscape consume; urban fields